2018
DOI: 10.1159/000489266
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco Cessation in Oncology Care

Abstract: Globally, tobacco use is a major modifiable risk factor and leading cause of many forms of cancer and cancer death. Tobacco use contributes to poorer prognosis in cancer care. This article reviews the current state of tobacco cessation treatment in oncology. Effective behavioral and pharmacological treatments exist for tobacco cessation, but are not being widely used in oncology treatment settings. Comprehensive tobacco treatment increases success with quitting smoking and can improve oncological and overall h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 54 publications
0
23
0
2
Order By: Relevance
“…Smoked and smokeless tobaccos not only negatively affect oral health but also affect clinical management of oral diseases and conditions [2]. However, it is one of the most modifiable risk factors of disease worldwide [3,4]. Many studies have shown that former smokers have better oral health than current smokers [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Smoked and smokeless tobaccos not only negatively affect oral health but also affect clinical management of oral diseases and conditions [2]. However, it is one of the most modifiable risk factors of disease worldwide [3,4]. Many studies have shown that former smokers have better oral health than current smokers [2,5,6].…”
Section: Introductionmentioning
confidence: 99%
“…The benefits of smoking cessation in cancer patients have led leading oncology societies to present guidelines stating that smoking habits should be addressed in all patients with cancer and that smoking cessation assistance should be provided for all smokers (Croyle et al, 2019;Kaiser et al, 2018;Price et al, 2019;Toll et al, 2013;Warren et al, 2014). Regardless of these guidelines, evidence of a gap between best and current practice for smoking treatment remains (Croyle et al, 2019;Kaiser et al, 2018;Price et al, 2019;Toll et al, 2013). Our findings endorse; first, the existence of cancer diagnosis as an open window for smoking cessation; and secondly, the potential health gains of implementing routine smoking cessation interventions in cancer care.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with cancer exhibit a high prevalence of distress symptoms, such as fatigue, pain, and anxiety. As for smoking status, these symptoms are often unaddressed during an oncology clinic visit due to similar barriers of time constraint and feelings of inability to adequately address symptoms [15][16][17]. Automated PRO measurement of tobacco use and treatment referral via the electronic health record (EHR) patient portal has not been studied, but may be effective in the oncology setting due to the potential to address barriers to care by enabling systematic administration of screening, automated referral for patients who smoke, repeated offering of treatment to smokers not interested in treatment, and potentially to reduce stigma associated with continued tobacco use after a cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high smoking relapse rate and the unique timeline of greatest relapse risk for patients with cancer, relying on provider assessment may result in a missed smoking lapse or relapse [19,20]. Clinicians vary in their knowledge of evidence-based methods for treating tobacco use and studies have shown that oncologists prefer smoking cessation treatment to be handled by another health care provider [16,21].…”
Section: Introductionmentioning
confidence: 99%